Assessment of Financial Judgment: Conceptual and Measurement Approaches, Metro Detroit, Michigan, 2014-2016 - Lichtenberg, Peter A. ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. Drawing on the principles of Whole Person Dementia Assessment (Mast, 2011) and Appelbaum and Grisso's (1988) decision-making model, this project developed a tool, the Lichtenberg Financial Decision Rating Scale (LFDRS). The conceptual model for the LFDRS questionnaire integrates the measurement of contextual variables with financial capacity assessment. The purpose of the study was to establish reliability and validity of the LFDRS and to collect data on normative financial decision-making by older adults. The researchers posited that as financial exploitation of older adults increases, investigation and prosecution of these cases remains difficult for criminal justice professionals who must balance protection of older adults with their right to autonomy; and that both under and over-protection of older adults can lead to damaging consequences. The project goal was to develop a set of new financial decision-making screening and comprehensive measures for criminal justice professionals and non-criminal justice professionals to aid in detecting and prosecuting financial exploitation of older adults. The LFDRS (described above) is meant to be used by mental health professionals, specially trained in assessment of older adults. In addition, the researchers developed a 10-item screening tool, the Lichtenberg Financial Decision Screening Scale or Short Scale (LFDSS), that was tested by multiple professionals working in diverse settings (e.g., APS workers, elder law attorneys, law enforcement personnel). Family members are another group that are often aware of an older adult's vulnerability to financial exploitation and therefore, the researchers developed the Lichtenberg Financial Decision Rating Scale -- Family and Friends version (LFDRS - Family and Friends also known as the LFDRS Informant) to allow concerned professionals to interview confidantes of older adults to help measure financial capacity of a loved one. This tool may be particularly useful for Adult Protective Services to interview multiple people regarding their concerns about an older adult. The collection contains 3 SPSS data files: LFDRS-Data-for-ICPSR.sav (200 cases, 109 variables) LFDRS_Informant-Data-for-ICPSR.sav (150 cases, 45 variables) LFDSS_Screener-Data-for-ICPSR.sav (213 cases, 24 variables)